Letter from Julia Morgan to Cousin Lucy and Cousin Pierre Le Brun, February 11, 1899 - Julia Morgan::::::author::: (1899)
On February 11, 1899 Julia Morgan wrote to her cousins Lucy and Pierre Le Brun. She thanks them for a calendar they sent and writes they've been occupied with work and being ill. She describes the construction going on in Paris in preparation for the Exposition Universelle in 1900. She recounts her trip with Avery to Fontainebleau and the operas they've been to recently. She explains that her ?cole des Beaux Arts work is mostly mathematics and that Avery has made friends at the atelier he is working at. She notes that M. Chaussemiche is kind and helpful. She ends the letter with pleasantries.